A novel eco-friendly recycling of food waste for preparing biofilm-attached biochar to remove Cd and Pb in wastewater. (15th August 2021) - Xing, Yonghui; Luo, Xuesong; Liu, Song; Wan, Wenjie; Huang, Qiaoyun; Chen, Wenli
Abstract: The development of green and sustainable cleaning technologies to properly reuse food waste and remove heavy metals in wastewater can avoid secondary damage to the environment. Our study proposes an innovative way to prepare an efficient adsorbent by growing bacterial biofilm in food waste and attaching them to biochar also prepared from food waste. Modification of the biochar by bacterial biofilm reduced the specific surface area but increased the average pore and the adsorption performance of Cd and Pb. Electrostatic adsorption and complexation by oxygen-containing functional groups were the main adsorption mechanisms for Cd and Pb by biofilm-attached biochar, and it was also easily recyclable by re-growth of the biofilm cultured by food waste. In wastewater containing both Cd and Pb, competitive adsorption between the two metal ions were observed on biofilm-attached biochar, while more functional groups were involved in removing Cd. This study proposes a new idea to reuse food waste as bio-modified biochar adsorbent and provides a promising strategy to remove heavy metals in wastewater by applying biofilm-attached biochar. Graphical abstract: Image 1 Highlights: High-efficiency adsorbent is prepared from multiple reuses of food waste. Electrostatic attraction and complexation dominate the removal of Cd 2+ and Pb 2+ . Prioritize adsorption of Pb 2+ but more functional groups participate in removing Cd 2+ . BAB is easily reused by re-growth of biofilm cultured by food waste.